The hysteretic behavior of recycled aggregate concrete-filled square steel tube columns. (1st November 2019) - Zhang, Xianggang; Gao, Xiang
Highlights: The test results of hysteretic behavior for S-RACFST column are discussed. A feasible prediction model of finite element is developed. Parameter analysis of hysteretic behavior is systematically investigated. Abstract: The research purpose was to explore the hysteretic behavior of recycled aggregate concrete-filled square steel tube (S-RACFST) columns. With the replacement ratio of recycled coarse aggregate and axial compression ratio as the variation parameters, 6 S-RACFST columns were carried out for the hysteretic behavior test, and the hysteretic behavior indexes such as failure mode, hysteretic curve and backbone curve were investigated through the test. Based on the experimental research, a feasible finite element analysis model was established. Meanwhile, the finite element expansion analysis of 32 full-scale specimens was carried out to reveal the influence of the design parameters on the hysteretic behavior indexes. It is shown that the damage of the specimen is mainly concentrated at the column roots, the square steel tubes bulge outwards in a "lantern" shape, and the interior recycled concrete has a large area of crushing and spalling. The hysteretic curves of all the test specimens are full and stable, the backbone curves are relatively complete with a smooth descending segment. The hysteretic behavior indexes of all full-scale specimens are less affected by the replacement ratio of recycled coarse aggregate, while the parameters such as steel ratio, aspect ratio and axial compression ratio have an enormous impact on the hysteretic behavior indexes such as peak load-bearing capacity, ductility and energy dissipation.